A Cost Analysis of the Jan Aushadhi Scheme in India - Kanchan Mukherjee (Kerman University of Medical Sciences, 2017)
Medicines constitute a substantial proportion of out-of-pocket (OOP) expenses in Indian households. In order to address this issue, the Government of India launched the Jan Aushadhi (Medicine for the Masses) Scheme (JAS) to provide cheap generic medicines to the patients (http://janaushadhi.gov.in/about_jan_aushadhi.html). These medicines are provided through the Jan Aushadhi stores established across the country. The objective of this study was to do a quick assessment for policy-makers regarding the objective of the JAS. Implications on cost savings for patients and policy implications of the scheme were analyzed. Secondary data sources were used to obtain prices of medicines under the JAS and prices of branded medicines of the same formulations. A cost analysis design was used. There are substantial differences between the JAS price and the cheapest branded medicine available in the market. However, not all JAS prices are lower than branded medicines. For example, the cheapest branded cefuroxime axetil (500 mg) (antibiotic) in the market is almost three times cheaper than its JAS price. Hence, there are cheaper brands available for some commonly prescribed medicines. From the policy perspective, it raises serious questions regarding the pricing of medicines in the JAS and its overarching goal. Since patients are dependent on physicians for medicine prescriptions and have little knowledge of the price variations among branded and generic medicines, the JAS may not provide the cheapest alternative for the patients. Hence, the government should urgently review the JAS prices to achieve its goal of providing low-cost affordable medicines.